2004
DOI: 10.1002/path.1564
|View full text |Cite
|
Sign up to set email alerts
|

Model of the early development of diffuse gastric cancer in E‐cadherin mutation carriers and its implications for patient screening

Abstract: Hereditary diffuse gastric cancer (HDGC) is a familial cancer syndrome caused, in 30-40% of cases, by germline mutations of the E-cadherin/CDH1 gene. The presence of clinically undetectable early gastric cancers has been previously reported in ten of ten prophylactic gastrectomies from germline E-cadherin mutation carriers. In the present study, detailed maps of the distribution of invasive cancers in nine of these ten stomachs were produced and precursor lesions of HDGC searched for. The nine gastrectomy spec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
199
0
8

Year Published

2007
2007
2020
2020

Publication Types

Select...
3
3
1

Relationship

3
4

Authors

Journals

citations
Cited by 238 publications
(221 citation statements)
references
References 12 publications
6
199
0
8
Order By: Relevance
“…The prophylactic gastric specimens generally show macroscopically no specific abnormalities at all [60][61][62]. Sometimes, subtle "pale" areas are visible endoscopically which may represent small foci of SRCs [48,63].…”
Section: Prophylactic Gastrectomymentioning
confidence: 99%
See 3 more Smart Citations
“…The prophylactic gastric specimens generally show macroscopically no specific abnormalities at all [60][61][62]. Sometimes, subtle "pale" areas are visible endoscopically which may represent small foci of SRCs [48,63].…”
Section: Prophylactic Gastrectomymentioning
confidence: 99%
“…Considering different studies which reported systematic complete mapping of total gastrectomies, there seems to be no restriction or convincingly preferred location of intramucosal SRCC in the stomach [60][61][62][64][65][66][67][68]. The foci were identified from cardia to prepyloric region and even in gastric metaplasia beyond the pylorus [48].…”
Section: Prophylactic Gastrectomymentioning
confidence: 99%
See 2 more Smart Citations
“…Several studies have shown that even though CDH1-mutation carriers had negative biopsies before prophylactic gastrectomy, cancer foci were detected in their gastrectomy specimens. 16,17 Management (please describe)…”
Section: How Is the Cost Effectiveness Of Alternative Diagnostic Methodsmentioning
confidence: 99%